The influence of street-scale built environment on transportation mode choice of travelers around metro stations - Liu, Yanan (E3S web of conferences, 2021)
To understand the determinants of transportation mode choice of travelers around metro stations, more and more built environment attributes have been studied and shown significant results. This study focuses on the impacts of street-scale built environment on the travelers around the metro stations. 754 trips stemming from 309 respondents were collected around Yingkoudao metro station in Tianjin, China. A multinomial logit model was estimated to predict transportation mode choice to/from the study area as a function of socio-demographic information, trip characteristics, and street-scale built environment attributes (including land use mix, road width, the shortest distance to the station, sidewalk width, number of lamps, greenery area, and traffic light presence) along the shortest route between the Yingkoudao metro station and the origin/destination around the station for the choice of metro+walk. The results show that not only the socio-demographic characteristics, but also the distance to the station, land use mix, and number of lamps significantly influence the choice of metro+walk.